Application of articaine in endoscopic endonasal dacryocystorhinostomy: a retrospective study - Liu, Shulin; Shui, Li; Liu, Zhaohui; Li, Qi (Frontiers in Medicine, 2024)
1) Background: To investigate the comparative effects of local anesthesia using lidocaine with adrenaline versus articaine with adrenaline in endoscopic endonasal dacryocystorhinostomy (EN-DCR); (2) Methods: This retrospective study included a total of 180 patients. These patients were categorized into two groups: the lidocaine group, which received 2% lidocaine (1:100,000 adrenaline), and the articaine group, which received 4% articaine (1:100,000 adrenaline) for local anesthesia. The study compared anesthesia efficacy, intraoperative pain levels, intraoperative bleeding, as well as differences in heart rate and blood pressure between the two groups; (3) Results:The articaine group demonstrated a significantly lower visual analogue scale (VAS) pain score when compared to the lidocaine group, measuring at 4.4±0.6 cm versus 5.0±1.0 cm, respectively (P＜ 0.0001). Additionally, the articaine group exhibited a higher anesthesia efficacy compared to the lidocaine group (89.0% vs. 76.6%, P=0.0487). Notably, the articaine group experienced less nasal mucosal bleeding during the surgery in contrast to the lidocaine group (P=0.004). However, there were no statistically significant differences in changes in blood pressure and heart rate between the two groups (P>0.05); (4) Conclusion: This study demonstrated that 4% articaine (1:100,000 adrenaline) has superior clinical effectiveness in comparison to 2% lidocaine (1:100,000 adrenaline) in EN-DCR.